Structural and biomechanical basis of mitochondrial movement in eukaryotic cells - Wu M (Dove Medical Press, 2013)
Min Wu,1 Aruna Kalyanasundaram,2 Jie Zhu1 1Laboratory of Biomechanics and Engineering, Institute of Biophysics, College of Science, Northwest A&F University, Yangling, Shaanxi, People's Republic of China; 2College of Pharmacology, University of Illinois at Chicago, Chicago, IL, USA Abstract: Mitochondria serve as energy-producing organelles in eukaryotic cells. In addition to providing the energy supply for cells, the mitochondria are also involved in other processes, such as proliferation, differentiation, information transfer, and apoptosis, and play an important role in regulation of cell growth and the cell cycle. In order to achieve these functions, the mitochondria need to move to the corresponding location. Therefore, mitochondrial movement has a crucial role in normal physiologic activity, and any mitochondrial movement disorder will cause irreparable damage to the organism. For example, recent studies have shown that abnormal movement of the mitochondria is likely to be the reason for Charcot–Marie–Tooth disease, amyotrophic lateral sclerosis, Alzheimer's disease, Huntington's disease, Parkinson's disease, and schizophrenia. So, in the cell, especially in the particular polarized cell, the appropriate distribution of mitochondria is crucial to the function and survival of the cell. Mitochondrial movement is mainly associated with the cytoskeleton and related proteins. However, those components play different roles according to cell type. In this paper, we summarize the structural basis of mitochondrial movement, including microtubules, actin filaments, motor proteins, and adaptin, and review studies of the biomechanical mechanisms of mitochondrial movement in different types of cells. Keywords: mitochondrial movement, microtubules, actin filaments, motor proteins, adaptin